Dynamic ethnic fractionalization and economic growth in the transition economies from 1989 to 2007 - Nauro F. Campos; Ahmad Saleh; Vitaliy S. Kuzeyev (Institute for the Study of Labor (IZA), 2009)
In their survey of the literature on ethnic fractionalization and economic performance, Alesina and La Ferrara (JEL 2005) identify two main directions for future research. One is to improve the measurement of diversity and the other to treat diversity as an endogenous variable. This paper tries to address these two issues: it investigates the effects of ethnic fractionalization on economic growth across countries using unique time-varying measures. We first replicate the finding of a weak effect of exogenous diversity on growth and then we show that accounting for how diversity changes over time and treating it as an endogenous variable makes a difference. Once diversity is instrumented (with lagged diversity and latitude), it shows a significant negative impact on economic growth which is robust to different specifications, polarization measures, econometric estimators, as well as to the use of an index of ethnic-religious-linguistic fractionalization.
Keywords: O11; Z12; O55; H1; 330; Ethnic diversity; fractionalization; polarization; growth; Ethnische Beziehungen; Segregation; Wirtschaftswachstum; Übergangswirtschaft; Schätzung; Transformationsstaaten